2021
DOI: 10.1186/s40708-021-00142-4
|View full text |Cite
|
Sign up to set email alerts
|

Person authentication based on eye-closed and visual stimulation using EEG signals

Abstract: The study of Electroencephalogram (EEG)-based biometric has gained the attention of researchers due to the neurons’ unique electrical activity representation of an individual. However, the practical application of EEG-based biometrics is not currently widespread and there are some challenges to its implementation. Nowadays, the evaluation of a biometric system is user driven. Usability is one of the concerning issues that determine the success of the system. The basic elements of the usability of a biometric s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Yap et al [29] investigated the potential of developing an EEG biometric system using a self-collected database of eight participants and an SVM classifier. The subjects were asked to perform two tasks: resting state with eyes closed, and visual stimulation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yap et al [29] investigated the potential of developing an EEG biometric system using a self-collected database of eight participants and an SVM classifier. The subjects were asked to perform two tasks: resting state with eyes closed, and visual stimulation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies relating to our proposed model are not common because most studies focus on identifying other biological signals, such as the iris and fingerprints [69,70], rather than brain waves. Many researchers also focused on classifying the brain signals recorded between cognitive tasks and non-tasks as performed by a user [61,71]. Moreover, previous studies have provided relatively low accuracy: Andreas M. Ray et al previously reported that the use of 27 healthy subjects achieved a mean classification accuracy of 75.30% [72].…”
Section: B Difficulty Classifying the One User From The Non-usersmentioning
confidence: 99%
“…Yap H. Y. et al [ 42 ] dealt with biometry based on two EEG acquisition protocols, namely eyes-closed and visual stimulation by words displayed on an LED screen. They created their own database of eight subjects.…”
Section: Introductionmentioning
confidence: 99%